Reaksi Pasar Modal Indonesia terhadap Pergantian Menteri Keuangan Baru: Analisis Event study pada Perusahaan yang Terdaftar dalam LQ45. - Kania Ilma Wisada; Riki Fahmi; Amalia Nur Chasanah; Vicky Oktavia; Rudi Kurniawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The change of the Minister of Finance has the potential to create uncertainty that could affect the capital market response. This study aims to analyze the Indonesian capital market's reaction to the change of the Minister of Finance in 2025 using an event study approach. The study sample consisted of 45 companies included in the LQ45 index with observation periods of 7, 14, and 30 days before and after the event. The variables used included abnormal returns, trading volume activity, and security return variability. Data analysis was performed using the Shapiro-Wilk normality test and the Wilcoxon signed-rank test. The results showed no significant differences in abnormal returns, trading volume activity, or security return variability across the observation periods. This finding indicates that the change of the Minister of Finance in 2025 did not generate a significant market reaction, either in terms of changes in stock returns, trading activity, or stock volatility. Therefore, information regarding the change of the Minister of Finance does not contain information content strong enough to significantly influence investor decisions in the Indonesian capital market.